New record for the distribution of the colonial hydroid Cordylophora caspia (Pallas, 1771) (Cnidaria: Hydrozoa) in Argentina - Deserti, Maria Irene (2015)
Cordylophora caspia is a colonial, athecate hydroid inhabiting both in freshwater and brackish habitats. Its global distribution is in part due to its ability to tolerate a wide range of salinity. It is considered an invasive species and its control is widely studied because of the industrial and ecological problems it causes in many environments. We report for the first time the occurrence of this hydrozoan in Nahuel Rucá Lake (Buenos Aires province, Argentina) with some notes on its internal and external morphology.